2020
DOI: 10.51791/njap.v46i1.1314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing maize with graded levels of sweet potato vine – cassava composite meal on growth performance, nutrient digestibility, carcass characteristics and economics of production of weaned rabbits

Abstract: The study was carried out to determine the feed value of replacing maize with graded levels of sweet potato vine – cassava composite meal (SPV-CCM) to rabbits. Five treatment diets were formulated to contain SPV-CCM inclusion levels of 0% (control), 25%, 50%, 75% and 100%. Thirty weaned rabbits of mixed breeds and sexes were used for the experiment. They were randomly allocated to five dietary treatments with one rabbit as a replicate in a completely randomized design. Feed and water were provided ad libitum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
2
Order By: Relevance
“…The daily weight gain of T1(0%) rabbit was also significantly (P<0.05) higher than that of all other treatments which followed a similar trend with the daily feed intake where T1(0%) had a value of 59.23g which was significantly (P<0.05) higher than that of all other treatments. The daily feed intake was between 33.78-59.23g which was lower than 66.28-83.24g and 48.24-74.36g reported by Shaahu and Tiough (2019) and Shaahu et al (2017), respectively. The daily weight gain ranged from 8.53-17.71g was higher than that of 4.95-5.23g reported by Uchegbe and Iyeghe-Erakpotobor (2015) who fed rabbits with sweet potato vine based diet supplemented with methionine and lysine, and also higher than and 9.04-12.94g reported by Shaahu and Tiough (2019) who fed rabbits sweet potato vinecassava composite meal.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The daily weight gain of T1(0%) rabbit was also significantly (P<0.05) higher than that of all other treatments which followed a similar trend with the daily feed intake where T1(0%) had a value of 59.23g which was significantly (P<0.05) higher than that of all other treatments. The daily feed intake was between 33.78-59.23g which was lower than 66.28-83.24g and 48.24-74.36g reported by Shaahu and Tiough (2019) and Shaahu et al (2017), respectively. The daily weight gain ranged from 8.53-17.71g was higher than that of 4.95-5.23g reported by Uchegbe and Iyeghe-Erakpotobor (2015) who fed rabbits with sweet potato vine based diet supplemented with methionine and lysine, and also higher than and 9.04-12.94g reported by Shaahu and Tiough (2019) who fed rabbits sweet potato vinecassava composite meal.…”
Section: Discussioncontrasting
confidence: 58%
“…The daily feed intake was between 33.78-59.23g which was lower than 66.28-83.24g and 48.24-74.36g reported by Shaahu and Tiough (2019) and Shaahu et al (2017), respectively. The daily weight gain ranged from 8.53-17.71g was higher than that of 4.95-5.23g reported by Uchegbe and Iyeghe-Erakpotobor (2015) who fed rabbits with sweet potato vine based diet supplemented with methionine and lysine, and also higher than and 9.04-12.94g reported by Shaahu and Tiough (2019) who fed rabbits sweet potato vinecassava composite meal. The Feed Conversion Ratio (FCR) value was not significantly different across the treatments groups, the values were higher than each other.…”
Section: Discussioncontrasting
confidence: 58%
“…Neem leaf extract (Azadirachta indica) is another phytochemical with a proven positive effect on broiler meat quality and also on the gene expression of antioxidant enzymes in the breast muscle. It should be, however, emphasized that fresh neem leaves can negatively affect broiler growth due to their high crude fiber content [29], because of which it is necessary to add them in the form of a dry leaf extract. The results of Nakamura et al (2022) [30] showed that the addition of 2.0% neem dry extract to broiler feed increased the expression of genes important for the activity of antioxidant enzymes in the breast muscle (Cu/Zn superoxide dismutase-SOD1, Mn superoxidase-MnSOD, glutathione peroxidase 7-GPX 7 and catalase-CAT).…”
Section: Phytonutrientsmentioning
confidence: 99%